Analysis of successful practices and determination of promising directions for implementing innovations in the sphere of housing and communal services in Russia - R. Kh. Mutolapov (Вестник университета)
Since the key direction of modern development is the introduction of digital technologies in order to optimise all the aspects of economic activity, the main focus of the work is aimed at analysing the current state and prospects for the introduction of innovations in the housing and utilities sector (here-inafter referred to as HUS) from the point of view of digitalisation of the industry.   To achieve this goal, we have used the analysis of statistical data in the context of the economic activities to determine the current level of innovative development of the HUS of Russia as well as individual indicators of the distribution and effectiveness of applying digital solutions in the industry. In the course of the work, it has been found that it significantly lags behind the average Russian indicators of innovation of innovative activity of companies, expenses on innovations as well as of modern products, works, and services. In the formation of the Russian “industry 4.0”, the HUS also demonstrates a significant lag in the development. The use of the most advanced and promising digital technologies is at an extremely low level, and the digital solutions applied in the activities of companies in the industry demonstrate extremely low efficiency rates, and most of them have virtually no significant impact on the work of the organisations. We believe that the negative experience of investing in the digital infrastructure is the reason for low involvement of the HUS companies in the fourth industrial revolution and low indicators of the innovative development on a national scale.